STRATEGI PENGEMBANGAN UKM BERBASIS INOVASI DI PROVINSI JAWA TIMUR: PERIODE 2010-2014 - Andre Hermanto; Ahmad Zafrullah Tayibnapis; Idfi Setyaningrum (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2016)
SME based on innovation in East Java is the stimulus for economic growth in Indonesia, with the potential to absorb a lot of labor so the problem of unemployment can be reduced, contribution to GDP (over 50%) and contribution to the growth rate. However unprepared SMEs, because of poor access to markets and lack of reliable human resources (many SMEs are still not being able to categorize the strengths, weaknesses, opportunities, and threats) affect SME based innovation in East Java has not been able to create strategies to expand its business. In other words, the potential of SMEs based on innovation in East Java has not been explored to the fullest. Based on the SWOT analysis, the strategy to develop the SME-based on innovation in East Java is strategy S-O (the orientation of excellent products to consumer preferences, fostering the SME-based on innovation, orientation to capital and credit facilities to the orientation of opportunity), S-T Strategy (institutional strengthening, creation of a conducive business), Strategy W-O (orientation clusters industrial centers of SMEs to various resources and information, production orientation to the broad market to market orientation specific, the orientation of the product packaging as it is to the modern consumer word of Mouth Marketing), Strategy W-T (based strategy resource to provide long-term competitiveness, establish close relationships with suppliers, training and education) and other supporting strategies (strategies to face of intense competition, the marketing of products strategies, strategies to choose business fields).